Hubungan Tingkat Pengetahuan Dengan Perilaku Remaja Putri Tentang Personal Hygiene Menstruasi di Poltekkes Kemenkes Surabaya Prodi DIII Keperawatan Tuban - Fitria, Vila Ana; Wahyurianto, Yasin; P, Teresia Retna (Jurnal Ilmiah Wahana Pendidikan, 2024)
Knowledge of personal menstrual sanitation allows women to misbehave in the act of personal menstrual sanitation which can cause vaginal discharge, venereal diseases, skin irritation and urinary tract infections (UTIs). The purpose of this research was to find out the relevance between knowledge level and behavior of young lad about menstrual personal cleanliness at the Ministry of Health Surabaya Polytechnic, DIII Nursing Study Program, Tuban. The study design uses correlation with a cross sectional approach. The population in this research were female students level 1 & 2 of the Surabaya Ministry of Health Polytechnic, DIII Nursing Study Program, Tuban. The sampling mode used is total sampling. The instrument in this study used a questionnaire, and the data was analyzed using chi-square test. Based on statistical check results obtained (p = 0.287 <0.05) which means there is no relationship between knowledge and personal hygiene menstruation behavior in DIII Nursing Study Program students in Tuban, with knowledge results in the good category 67.1% and behavior in the sufficient category 48 .2%. It is expected that the respondent will carry out personal menstrual hygiene actions properly and correctly.